The effectiveness of using website in learning Arabic language for the purpose of tourism: a case study among students at College Poly-Tech MARA (KPTM) - Abdul Ghani, Mohammad Taufiq; Sahrir, Muhammad Sabri; Wan Daud, Wan Ab Aziz (2015)
This study examined the effectiveness of using website in learning Arabic language for the purpose of tourism at the Department of General Studies at the College of Poly-Tech MARA, Kelantan Darul Naim. Descriptive study is used to describe briefly about the Arabic Language for Specific Purposes and analyze the effectiveness of website as a main tool in learning activities. This paper is done based on questionnaires and observation in class HFA-1023 (Bahasa Arab Asas Untuk Pelancongan dan Hospitaliti). A questionnaire was distributed to 43 students that have been registered for this course. The descriptive quantitative analysis was used to analyze the data by using SPSS. In general, the finding provides evidence that using website in learning the Arabic language for the purpose of tourism was efficient, and the researcher found that new technologies represent a valuable and effective support for students in learning language for specific purposes.